Faktor-Faktor yang Mempengaruhi Struktur Modal pada Perusahaan Pertambangan di Bursa Efek Indonesia Periode 2015-2018 - Nurul Aryanti; Riana Rachmawati Dewi; Purnama Siddi (Ekonomis: Journal of Economics and Business, 2020)
This study examines and analyzes the factors that influence capital structure.  Independent variables in this study are company size, liquidity, profitability and asset structure.  The population in this study are mining companies listed on the Indonesia Stock Exchange for the 2015-2018 period.  The sample selection technique uses purposive sampling and 12 company samples are obtained within a period of 4 years so that 48 company samples are obtained.  The data analysis method used in this study is panel data regression.  Hypothesis testing is done using the t test and the F test. The panel data regression test results show that simultaneously company size, liquidity, profitability and asset structure have an influence on capital structure.  While partially the variables that significantly influence the capital structure are company size.  While the liquidity, profitability and asset structure variables do not significantly affect the capital structure.